Financial accounting theory and analysis : text and cases - Schroeder, Richard G.; Clark, Myrtle; Cathey, Jack M. (2023)
"Accounting education has experienced many dramatic changes over the life of this accounting theory text. The publication of the fourteenth edition represents over forty years in its evolution. At its inception, much of what was then considered theory was, in reality, rote memorization of rules. In recent years, the globalization of the economy has affected the skills necessary to be a successful accountant and has caused accounting educators to develop new methods of communicating accounting education. Emphasis is now being given to the incorporation of ethics into the curriculum, the analysis of a company's quality of earnings and sustainable income, the use of the World Wide Web as a source of information, the international dimensions of accounting, the development of critical thinking skills, the development of communication skills, and the use of group projects to develop cooperative skills. This edition of the text is a further extension of the refocusing of the material to suit the needs of accounting professionals into the twenty-first century"--
Includes bibliographical references and index.
Keywords: Accounting; Accounting -- Problems, exercises, etc